Ki Hadjar Dewantara's Thinking As A Model of Educational Leadership and Inheritance of National Values - Adiyati, Rini; Handoyo, Eko; Indriyanti, Dyah Rini (Proceedings of International Conference on Science, Education, and Technology, 2024)
Along with changes and developments over time, as well as the rise of national plus schools developed using British and Western systems, Ki Hajar Dewantoro's leadership pattern began to be eroded by the current of change. Many leaders today tend to adhere to leadership references originating from Western cultural philosophy, even though they live and lead within the cultural realm of Javanese society in Indonesia. The impact is that the leadership pattern feels disconnected and underdeveloped. This article aims to discuss analyzing the concept of leadership and character of Ki Hadjar Dewantara in its implications in Indonesian schools. The research method used is qualitative, with an interdisciplinary approach. These methods and approaches are used so that the discussion can be carried out more comprehensively and in depth. The results of this research show that the down-to-earth educational leadership pattern initiated by Ki Hadjar Dewantara is very necessary to build educational character values in Indonesia. These concepts and principles are very necessary, because they are connected to the preservation of Indonesian cultural values which are full of diversity.